Analisis Jaringan Isu #percumalaporpolisi Sebagai Bentuk Rendahnya Kepercayaan Netizen Terhadap Kepolisian di Twitter - Khairul Syafuddin (Universitas Majalengka, 2022)
The emergence of social media makes it easy for people to produce their own public opinion. Public opinion is not only formed by the mass media. People who become netizens on social media are able to shape this public opinion. One of them through Twitter. One of the public opinions that had become a trending topic on Twitter was #percumalaporpolisi. The hashtag became popular because the public considered the police performance to be lower. This study aims to see how large the Twitter network is formed from the hashtag #percumalaporpolisi. In addition, this study also looks at the discourse that is formed from the tweets produced by netizens on Twitter. This study uses the method of Social Media Network Analysis (SMNA) and critical discourse analysis with the Fairclough approach. Twitter tweets data were taken as many as 2.500 posts related to #percumalaporpolisi from December 12 to December 20, 2021. The results of this study see that during that time the issue of #percumalaporpolisi had increased dramatically on December 19, 2021. The increase in issues was triggered by related issues. #TangkapBaharSmith. In addition, netizens also raised several discourses in their tweets. The tweets that have a high enough intensity are related to the CINTA NKRI. The hashtag #percumalaporpolisi also broadens the meaning of individual officers.